The Landscape as an Asset in Southern European Fragile Agricultural Systems: Contrasts and Contradictions in Land Managers Attitudes and Practices (Landscape Research)
Abstract Transition theories suggest that there is a spatial, temporal and structural co-existence of several processes of transition from productivism to post-productivism going on in rural areas in multiple combinations resulting in a more complex, contested, variable mix of production, consumption and protection goals. This is particularly true for South European landscapes dominated by extensive agro-silvo-pastoral systems. The fragile agricultural sector is in some cases just entering the productivist phase, let alone moving towards post-productivism both in terms of discourse and management practices. At the same time, these are landscapes increasingly valued by society, and this demand should encourage new strategies for farm survival and new ways of managing the land. But such new strategies require a paradigm shift, not only in policy goals and formulation, but also in farmers’ attitude towards their role and their management goals. In this paper, the question addressed is how the land managers within this system, facing multiple transition options, are choosing different management paradigms, in the complex range between productivism and post-productivism. Based on a farm survey in southern Portugal, a typology of land managers is produced, aiming to grasp the combination between their management practices in the farm and their expressed attitudes towards farm management and the role of their farm in the landscape. Results reveal some inconsistencies between land managers’ intentions and their landscape outcomes, in an opposite sense to what has been earlier identified in Northwestern Europe. Even if they manage a multifunctional system, their self-concept is dominantly productivist and not affected by the public expectations of multifunctionality. This tension may reflect contradictions in the policy framework and, at the same time, raises challenges which the existing policy mechanisms do not consider.